Analysis of the global transcriptome of longan (Dimocarpus longan Lour.) embryogenic callus using Illumina paired-end sequencing - Lai, Zhongxiong (BioMed Central, 2013)
BACKGROUND: Longan is a tropical/subtropical fruit tree of great economic importance in Southeast Asia. Progress in understanding molecular mechanisms of longan embryogenesis, which is the primary influence on fruit quality and yield, is slowed by lack of transcriptomic and genomic information. Illumina second generation sequencing, which is suitable for generating enormous numbers of transcript sequences that can be used for functional genomic analysis of longan. RESULTS: In this study, a longan embryogenic callus (EC) cDNA library was sequenced using an Illumina HiSeq 2000 system. A total of 64,876,258 clean reads comprising 5.84 Gb of nucleotides were assembled into 68,925 unigenes of 448-bp mean length, with unigenes ≥1000 bp accounting for 8.26% of the total. Using BLASTx, 40,634 unigenes were found to have significant similarity with accessions in Nr and Swiss- Prot databases. Of these, 38,845 unigenes were assigned to 43 GO sub-categories and 17,118 unigenes were classified into 25 COG sub-groups. In addition, 17,306 unigenes mapped to 199 KEGG pathways, with the categories of Metabolic pathways, Plant-pathogen interaction, Biosynthesis of secondary metabolites, and Genetic information processing being well represented. Analyses of unigenes ≥1000 bp revealed 328 embryogenesis-related unigenes as well as numerous unigenes expressed in EC associated with functions of reproductive growth, such as flowering, gametophytogenesis, and fertility, and vegetative growth, such as root and shoot growth. Furthermore, 23 unigenes related to embryogenesis and reproductive and vegetative growth were validated by quantitative real time PCR (qPCR) in samples from different stages of longan somatic embryogenesis (SE); their differentially expressions in the various embryogenic cultures indicated their possible roles in longan SE. CONCLUSIONS: The quantity and variety of expressed EC genes identified in this study is sufficient to serve as a global transcriptome dataset for longan EC and to provide more molecular resources for longan functional genomics.